European drug report / 2021 (European drug report trends and developments, 2021)
The Trends and Developments report presents the EMCDDA's latest analysis of the drug situation in Europe. Focusing on illicit drug use, related harms and drug supply, the report contains a comprehensive set of national data across these themes and key harm reduction interventions.